Playing Futsall Development Based on Model Variations - Marlina, Yeni; Zahara, Zahara; Syamsulrizal, Syamsulrizal; Iqbal, Muhammad (INSPIREE: Indonesian Sport Innovation Review, 2023)
The  purpose  of  the study. Universitas Syiah Kuala students who attended the Futsal TP course numbered one hundred and fifty people. And researchers determine the sample between forty five to fifty people. Materials and methods. The steps are adapted from the book "Educational Research" by Borg and Gall which consists of ten steps Results. The following: first, a total of sixty-eight point fifty-six percent of participants stated that futsal games were not fun; second, seventy-three point fifty-four percent stated that the training skill model was less varied; third, ninety-three point seventy-seven percent of participants agreed that they needed new and pleasant variations, fourth, sixty-three point sixty-nine percent of futsal sports skills using and the five players. Conclusions. trainers who need to develop models for futsal sports skills are one hundred percent.